2016
DOI: 10.1002/lt.24401
|View full text |Cite
|
Sign up to set email alerts
|

Risk analysis of ischemic‐type biliary lesions after liver transplant using octogenarian donors

Abstract: The use of octogenarian donors to increase the donor pool in liver transplantation (LT) is controversial because advanced donor age is associated with a higher risk of ischemic-type biliary lesions (ITBL). The aim of this study was to investigate retrospectively the role of a number of different pre-LT risk factors for ITBL in a selected population of recipients of octogenarian donor grafts. Between January 2003 and December 2013, 123 patients underwent transplantation at our institution with deceased donor gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 46 publications
(69 reference statements)
5
33
1
Order By: Relevance
“…This is in line with the factors that were identified by Ghinolfi et al including a history of diabetes . Diabetes is more often present in older donors and may have a stronger and more chronic effect on the vasculature and parenchyma in older donor livers . Diabetes, therefore, seems to be an important risk factor that should be avoided when possible.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is in line with the factors that were identified by Ghinolfi et al including a history of diabetes . Diabetes is more often present in older donors and may have a stronger and more chronic effect on the vasculature and parenchyma in older donor livers . Diabetes, therefore, seems to be an important risk factor that should be avoided when possible.…”
Section: Discussionsupporting
confidence: 87%
“…The utilization rate of livers ≥70 years old was even slightly higher at 72% when livers that were used for retransplantations were included (data not shown). These rates are very high in comparison to other studies who report usage rates of approximately 60% and 52%‐63% for liver donors ≥70 years and ≥80 years old, respectively . It does, however, correspond with usage in the United States where 74% of livers of 70 years and older are used for transplantation .…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…To support this hypothesis, a recent study on 88 primary LTs demonstrated a significant association between donor DM and ischemic-type biliary lesions with an HR of 9.5 ( P = 0.009), suggesting that DM promotes chronic changes in the biliary vessels, thereby increasing susceptibility to IRI. 22 …”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, we thank Ghinolfi et al (1) for the precious research they are carrying on, and we encourage other groups to share their experience on octogenarian liver grafts. …”
mentioning
confidence: 88%